Surgical Management of Mandibular Angle Fracture in an Adolescent Patient: A Case Report - Nabilla Soraya Fajarina Putri; Annisa Anindya; Friska Auriani; Hendra Sukawijaksa (Maranatha Christian University, 2025)
Introduction: Mandibular fractures in pediatric and adolescent patients pose unique challenges due to active facial growth and differing biomechanical properties of bone. Treatment planning in adolescents must carefully balance surgical stability and preservation of growth potential. The mandibular angle is a common site of fracture, often resulting from high-impact trauma. Aim of this case report is to describes the surgical management of a right mandibular angle fracture in adolescent using open reduction and internal fixation (ORIF) combined with intermaxillary fixation. Case report: A 16-year-old male presented with right jaw pain persisting for one week following a motor vehicle accident. Extraoral examination revealed facial asymmetry, edema, and hematoma in the right chin region. Intraoral findings included trismus, edema and erythema in the gingiva of region 48, posterior open bite, and malocclusion. Panoramic radiography revealed a step deformity at the right mandibular angle. The diagnosis was a right mandibular angle fracture and treated with ORIF followed by intermaxillary fixation using arch bars. Three week postoperative follow-up, the fracture was well stabilized, occlusion had returned to normal, and minimal postoperative complications were noted. Discussion: ORIF and temporary intermaxillary fixation provided adequate stabilization without interfering with developing structures. Prompt intervention and careful surgical planning resulted in proper fracture healing and restoration of function. Conclusion: ORIF combined with intermaxillary fixation is a reliable treatment option for mandibular angle fractures in adolescents. Early recognition, proper surgical planning, and appropriate follow-up are essential to achieve favorable functional and esthetic outcomes without compromising facial growth. Keywords: Adolescent, Intermaxillary fixation, Mandibular angle fracture, ORIF